Ecological and environmental characteristics of a seagrass-dominated hypersaline coastal Mediterranean lagoon: a multidisciplinary approach - A. Ramfos; A. Alysandratou; O. Katsani; S. Faulwetter; K. Nikolakopoulos; P. Avramidis (Aquatic Sciences, 2024)
In the present paper, sedimentological, water physicochemical data and biological benthic assemblages are compiled to provide an integrated environmental assessment of a protected shallow Mediterranean lagoon with a long history of management interventions (Klisova Lagoon, Western Greece). Satellite remote sensing techniques were used for mapping the seagrass Cymodocea nodosa (Ucria) Asch, which presents an extensive expansion in the study area. The results showed that Klisova is a hypersaline, well-oxygenated lagoon presenting changes in temperature, salinity, pH and dissolved oxygen over the course of 1 year, but largely lacks any spatial differentiation other than an east–west gradient in salinity in spring and summer. Sediment was classified as silty sand to silt, rich in total organic carbon (TOC), total nitrogen (TN) and total phosphorus (TP). The benthic community was characterised by a high species richness and the presence of marine species, without a clear spatial pattern. The multivariate-AZTI’s marine biotic index (M-AMBI) showed that the ecological quality of the macrobenthos was good in most stations. C. nodosa covered over 70% of the lagoon area and formed meadows even in the eastern part of the lagoon where salinity during spring and summer was close to the reported upper tolerance limit of the species (> 50). The present multidisciplinary approach provides valuable baseline information on various components of the ecosystem which can be used as a basis for management bodies and future conservation plans for the lagoon.